2015
DOI: 10.7567/apex.8.065503
|View full text |Cite
|
Sign up to set email alerts
|

Improved efficiency of electrodeposited p-CuO/n-Cu2O heterojunction solar cell

Abstract: We report electrodeposition of n-type cuprous oxide (Cu 2 O) films on p-type CuO films electrodeposited on Ti substrates for forming p-CuO/n-Cu 2 O heterostructures. X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis revealed that the films had good structural quality, with substrates being well-covered by the films. The p-CuO/n-Cu 2 O heterojunctions exhibited good photovoltaic properties and diode characteristics. The surfaces of Cu 2 O films subject to ammonium sulfide treatment exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The main reason that copper oxides are still attracting the attention of the scientific community is owing to the theoretical PCE of Cu 2 O and CuO, which is estimated using the Shockley and Queisser (SQ) [7] predictor to be 20% and 30%, respectively [8]. Although, to the best of our knowledge, data for the PCE of Cu 4 O 3 do not exist, some authors have suggested that it could be a better absorbing material than the previously characterized copper materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…The main reason that copper oxides are still attracting the attention of the scientific community is owing to the theoretical PCE of Cu 2 O and CuO, which is estimated using the Shockley and Queisser (SQ) [7] predictor to be 20% and 30%, respectively [8]. Although, to the best of our knowledge, data for the PCE of Cu 4 O 3 do not exist, some authors have suggested that it could be a better absorbing material than the previously characterized copper materials [9].…”
Section: Introductionmentioning
confidence: 99%
“…The passivation along with annealing was successfully used to improve the efficiency of Ti/p‐CuO/n‐Cu 2 O/Au solar cell. The cell yielded a power conversion efficiency of 0.64%, which to the best of our knowledge is the highest reported efficiency for a CuO‐based solar cell . Further studies with regard to structural and thermal stability of passivated and annealed Cu 2 O thin films will provide important information for improving the performance of such devices.…”
Section: Introductionmentioning
confidence: 81%
“…It has been utilized in numerous applications including photocatalysis, supercapacitors, lithium ion batteries, infrared photo detectors, biosensors, and gas sensors [2][3][4][5][6][7][8]. It is an ideal absorber material for solar cells, as its optical absorption edge lies in the range between 1.2 eV and 1.9 eV [9,10]. It is an excellent sensing material.…”
Section: Introductionmentioning
confidence: 99%